Detection and Molecular Characterization of Gyrovirus Galga 1 in Chickens in Northern Vietnam Reveals Evidence of Recombination - Giang Thi Huong Tran; Le Thi My Huynh; Hieu Van Dong; Amonpun Rattanasrisomporn; Autchara Kayan; Dao Anh Tran Bui; Jatuporn Rattanasrisomporn (Animals)
In total, 126 tissue-pooled samples were collected from suspected sick chickens showing signs of stunted growth, weakness, and diarrhea in five provinces/cities in Northern Vietnam. The Gyrovirus gala 1 (GyVg1) genome was detected in 26 (20.63%) of the 126 chicken samples based on a polymerase chain reaction assay. The five Vietnamese GyVg1 genomes obtained were all 2.375 nucleotides in length. Among them, the nucleotide identical rates ranged from 94.01% to 100%. Phylogenetic analysis of the complete genomes revealed that the current five GyVg1 strains belonged to different branches at two levels: GyVg1 II (two of five strains) and GyVg1 III (three of five strains). The Vietnamese GyVg1 strains were generically clustered with the Japanese and Chinese strains. Some amino acid substitutions were found in VPs 1, 2, and 3 of the Vietnamese GyVg1 strains. In addition, three and two positive selection sites of VPs 1 and 3 were detected, respectively. A recombination event occurred and generated a recombination Chicken/Vietnam/AGV/VNUA-TN12/2023 strain. These findings indicate the first evidence of GyVg1 viruses circulating in commercial chicken flocks in Vietnam.